Digital Literacy in Mathematics Education: Transformative Praxis in Nepal - Bhatt, Krishna Prasad (Interdisciplinary Research in Education, 2021)
This study was carried out to sightsee amidst digital literacy together with transformative praxis of undergraduate teachers and the existing situation of the digital divide in Nepal. The entire research process of the study was guided by the post-positivism paradigm followed by survey design. This was a cross-sectional survey of school teachers were chosen as a sample by using the purposive sampling method within 183 participants. Document analysis and SPSS v.23 was used for multivariate data analysis that reaping intensive information regarding the current situation of Information Communication Technology (ICT) literacy in the context of Nepal.The results of the study reveal that there is a substantial issue of the digital divide and fear of digital dictatorship among the teachers to continue their job for the long run and compete in the twenty-first century. However, teachers are doing their job with utmost efficiency even with the lack of knowledge of digital technology.